MANGANESE (Mn) MINERAL DELINIATION AT THE “NAMASTE” FIELD BASED ON INDUCED POLARIATION (IP) METHOD - Virnanda Eka Cahyaningtyas; Y Yatini (Jurnal Geosaintek, 2026)
Indonesia is one of the world's leading producers of manganese (Mn). Manganese is one of the essential elements required by humans and industry, making the exploration of manganese minerals crucial. This exploration often utilises geophysical methods. Research has been conducted on the “Namaste” field area located in Tulungagung Regency, East Java. The study aims to determine the presence and distribution of manganese minerals using the Induced Polarisation (IP) method, thereby enabling the identification of the lithology and the presence of manganese minerals in the study area. Measurements were made on 10 trajectories using a dipole-dipole configuration with a = 10 and a = 20 meters and n = 1-8. The measurement trajectory spans an area of 400 m x 400 m, with a length ranging from 100 to 260 meters. Data were processed using Res2DInv and other software such as Surfer, Oasis Montaj, CorelDraw, Rockwork, and Leapfrog. The results show the distribution of resistivity values in the range of (5-4500) Ohm-m and chargeability values of (1-295) msec. Low resistivity values, below 100 Ohm-m, are interpreted as indicating carbonate mudstone, while medium resistivity values (100-2000 Ohm-m) are interpreted as indicating limestone. High resistivity values >2500 Ohm-m are interpreted as intrusive igneous rocks. The presence of manganese minerals is spread at a depth of <27 meters with a high chargeability value of >100 msec. The distribution of manganese minerals is dominated in the central and northern areas of the study area.